Aktivitas farmakologi dan fitokimia ekstrak Moringa oleifera lam. terhadap sistem reproduksi pria dan wanita: scoping review - Anggarany, Ariska Deffy (Universitas Muhammadiyah Magelang, 2025)
Reproductive health is an important part of life continuity. Moringa oleifera plant is reported to have benefits on growth and reproduction that have been tested on animals, such as steroid alkaloids, alkaloid-pyricine, pyrrolidine, phenolics, steroid glycosides, saponins and triterpenoids. This study aims to demonstrate the pharmacological activity of Moringa oleifera Lam. extract as an antifertility agent in the male and female reproductive systems. This study assessed the phytochemical compounds and antifertility effects of moringa on reproductive parameters in both men and women. This study was conducted through a literature study based on an online database search by combining Boolean search terms (“AND”, “OR”) in the electronic databases PubMed, ScienceDirect and Google Scholar. There were 15 articles that met the inclusion and exclusion criteria of the study. Several phytochemical compounds such as tannins, alkaloids, phenols, flavonoids, saponins and anthraquinones were reported in extracts of both flowers, stems, seeds and leaves of the moringa plant. The effects of these compounds have the potential to improve sperm quality, increase testosterone production in men, and affect hormone levels and estrus cycles in female reproduction. These findings support the role of Moringa oleifera as an antifertility agent in various reproductive parameters in both men and women.